2018
DOI: 10.1200/jco.2017.76.8093
|View full text |Cite
|
Sign up to set email alerts
|

Positron Emission Tomography–Guided Therapy of Aggressive Non-Hodgkin Lymphomas (PETAL): A Multicenter, Randomized Phase III Trial

Abstract: Purpose Interim positron emission tomography (PET) using the tracer, [F]fluorodeoxyglucose, may predict outcomes in patients with aggressive non-Hodgkin lymphomas. We assessed whether PET can guide therapy in patients who are treated with cyclophosphamide, doxorubicin, vincristine, and prednisone (CHOP). Patients and Methods Newly diagnosed patients received two cycles of CHOP-plus rituximab (R-CHOP) in CD20-positive lymphomas-followed by a PET scan that was evaluated using the ΔSUV method. PET-positive patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
202
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 185 publications
(225 citation statements)
references
References 32 publications
12
202
1
4
Order By: Relevance
“…Increasing evidence has illustrated that the semiquantitative method using SUVmax reduction is more accurate than visual analysis, based on DS to identify subgroups of patients with significantly different prognoses. 6,[14][15][16][17] Our results are consistent with those of other studies and confirm that ΔSUVmax evaluation (cutoff value of 74%) of iPET/CT is an independent predictive factor for DLBCL patients. Survival analysis revealed that patients with ΔSUVmax ≥ 74% had a significantly better PFS and OS than did patients with ΔSUVmax < 74%, irrespective of DS scores (Figure 4).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Increasing evidence has illustrated that the semiquantitative method using SUVmax reduction is more accurate than visual analysis, based on DS to identify subgroups of patients with significantly different prognoses. 6,[14][15][16][17] Our results are consistent with those of other studies and confirm that ΔSUVmax evaluation (cutoff value of 74%) of iPET/CT is an independent predictive factor for DLBCL patients. Survival analysis revealed that patients with ΔSUVmax ≥ 74% had a significantly better PFS and OS than did patients with ΔSUVmax < 74%, irrespective of DS scores (Figure 4).…”
Section: Discussionsupporting
confidence: 91%
“…Increasing evidence has illustrated that the semiquantitative method using SUVmax reduction is more accurate than visual analysis, based on DS to identify subgroups of patients with significantly different prognoses . Our results are consistent with those of other studies and confirm that ΔSUVmax evaluation (cutoff value of 74%) of iPET/CT is an independent predictive factor for DLBCL patients.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The latter regimens are in use for more than a decade and produce excellent results in Burkitt lymphoma at the expense of considerable, nonetheless temporary toxicities . With regard to this toxicity and in light of the well‐documented failure of first‐line treatment intensification in unselected DLBCL patients, the efficacy of the BL‐type protocols has only been tested systematically in chemotherapy‐refractory DLBCL as determined by interim positron emission tomography (iPET) . Nevertheless, DLBCL as well as mantle cell lymphoma (MCL), B‐cell non‐Hodgkin lymphomas transformed from an indolent variant (tB‐NHL) and T‐cell non‐Hodgkin lymphomas (T‐NHL) sometimes present in a clinical constellation where (R)‐CHOP is considered inadequate.…”
Section: Introductionmentioning
confidence: 99%